Brief intervention for students with methamphetamine use disorders: A randomized controlled trial - Manit Srisurapanont (2018)
This study evaluated the short-term (eight-week) benefits of brief intervention (BI) in students aged 14-19 years old who met the DSM-IV diagnostic criteria for methamphetamine (MA) dependence or abuse. The participants were randomly assigned to receive two 20-minute sessions of BI or one 15-minute session of psychoeducation (PE). Primary outcomes of interest were the decrease of MA use in days of use (per week) units and MA tablets used (per day when used). All outcomes were assessed at baseline (week 0), week 4, and week 8 (endpoint). A total of 48 participants were enrolled in the study (24 on BI and 24 on PE treatment). At week 4, the numbers of dropouts in the BI and PE groups were 7 and 5, respectively. The frequency and amount of MA use decreased significantly in both groups. At week 8, the days of MA use had decreased in the BI group by a significantly larger number than in the PE group (t = 2, df = 34, p = 0.04). BI appears to have some minimal short-term benefits for adolescents with MA use disorders. It may decrease the number of days that MA is used. Copyright © American Academy of Addiction Psychiatry.